The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1164/rccm.201711-2174oc
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Outcomes in Idiopathic Pulmonary Fibrosis Using Automated Computed Tomographic Analysis

Abstract: Short running head: IPF baseline outcome prediction Word count: 4310 wordsThis article has an online data supplement, which is accessible from this issue's table of content online at www.atsjournals.org At a Glance: Quantification of CT parenchymal patterns in idiopathic pulmonary fibrosis using computer tools has been suggested as a method that can improve on mortality prediction using visual CT scoring. As computer technology advances, it has now become possible to study CT parenchymal features that have no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
105
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 155 publications
(110 citation statements)
references
References 44 publications
4
105
0
1
Order By: Relevance
“…We identified relatively stronger inverse relationships between lung function indices and vessel volume in the upper/middle zones compared to the lower lung zones. These results are in line with previous reports of stronger links between FVC decline and mortality in baseline upper/middle zone VRS when compared to lower zone VRS in patients with IPF . MRI studies have demonstrated that fibrotic tissues show delayed contrast enhancement when compared to morphologically normal appearing lung in lung fibrosis patients .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We identified relatively stronger inverse relationships between lung function indices and vessel volume in the upper/middle zones compared to the lower lung zones. These results are in line with previous reports of stronger links between FVC decline and mortality in baseline upper/middle zone VRS when compared to lower zone VRS in patients with IPF . MRI studies have demonstrated that fibrotic tissues show delayed contrast enhancement when compared to morphologically normal appearing lung in lung fibrosis patients .…”
Section: Discussionsupporting
confidence: 92%
“…Whilst the majority of automated parenchymal features reflect patterns scored visually by radiologists, there has been increasing focus on novel CT patterns that computer tools can recognize, but which cannot be quantified visually. An example is the vessel‐related structures (VRS) readout determined by CALIPER, which was able to powerfully predict outcome in patients with IPF . However, until now, CALIPER has been the only tool used to evaluate vasculature in patients with lung fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, CT densitometry, especially the area right of the inflexion point in HRCT histogram was reported to correlate with lung function decline [71]. JACOB et al [72] reported recently that a computer scoring based quantification of parenchymal patterns including vessel-related structure scores predicted IPF mortality and functional decline in IPF. Hyperpolarised xenon-129 magnetic resonance imaging could be a potential non-invasive method for estimating gas-exchange impairment in IPF, as this inert gas is able to image the distribution in airspaces as well as in the red blood cells of the vessels and in tissue of interstitial parenchyma [73].…”
Section: Radiological Biomarkersmentioning
confidence: 99%
“…IPF was diagnosed by multidisciplinary teams in patients receiving two non-contrast volumetric CT scans between 5 and 30 months apart as part of their clinical care. Previous baseline analyses of IPF patients 5 made it apparent that variable initiation time of antifibrotics and varied dosages, durations and types of antifibrotic medication in study participants had a profound confounding effect on mortality relationships. Specifically, patients not uncommonly began antifibrotics between the first and second CTs and in most cases after the second CT. Consequently, cardinal analyses in the current manuscript were restricted to patients not receiving any anti-fibrotic therapy (n=118).…”
Section: Methodsmentioning
confidence: 99%